2010
DOI: 10.1186/1754-6834-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Furfural induces reactive oxygen species accumulation and cellular damage in Saccharomyces cerevisiae

Abstract: BackgroundBiofuels offer a viable alternative to petroleum-based fuel. However, current methods are not sufficient and the technology required in order to use lignocellulosic biomass as a fermentation substrate faces several challenges. One challenge is the need for a robust fermentative microorganism that can tolerate the inhibitors present during lignocellulosic fermentation. These inhibitors include the furan aldehyde, furfural, which is released as a byproduct of pentose dehydration during the weak acid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
226
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(246 citation statements)
references
References 50 publications
11
226
0
9
Order By: Relevance
“…In addition to energy efficiency, the use of excessive pre-treatment reaction conditions results in the formation of compounds which act as inhibitors to downstream processes including enzymatic saccharification and fermentations (Palmqvist et al, 1998;Chheda et al, 2007;Allen et al, 2010). These compounds are often the result of thermal or chemical degradation of liberated sugars (to furan based inhibitors) or lignin (to phenolic/hydroxycinnamic acid based inhibitors).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to energy efficiency, the use of excessive pre-treatment reaction conditions results in the formation of compounds which act as inhibitors to downstream processes including enzymatic saccharification and fermentations (Palmqvist et al, 1998;Chheda et al, 2007;Allen et al, 2010). These compounds are often the result of thermal or chemical degradation of liberated sugars (to furan based inhibitors) or lignin (to phenolic/hydroxycinnamic acid based inhibitors).…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of furfural have inhibitory effects on yeast growth 5) and fermentation 6) , but the mechanism of inhibition is still under investigation. For example, the addition of furfural is shown to induce the generation of reactive oxygen species in Saccharomyces cerevisiae 7) . Comprehensive analyses of the inhibitory mechanisms of furfural, 5-HMF, and acetic acid on yeast growth and fermentation 8) 10) have shown that more genes are down-regulated than up-regulated in the presence of these compounds 8) .…”
Section: Introductionmentioning
confidence: 99%
“…5-HMF, furfural, acetic acid, formic acid and levulinic acid to determine the tolerance level to the inhibitors tested. These inhibitor have been shown to have toxic effects on cells which causing damage by inhibiting enzymes produced by microorganisms (Cantarella et al, 2004;Allen et al, 2010) or by impeding enzymes responsible for fermentation which then affecting their membrane integrity (Mills et al, 2009;QueĂŹmeĂŹneur et al, 2012). However, the result showed that both A. pullulans LBF-3-0074 and S. etchellsii LBF-3-0034 strains were still optimally grown in the 5-HMF-added medium ( Figure 2A).…”
Section: The Characteristic Of Yeasts In Various Inhibitors Compoundsmentioning
confidence: 50%